Impact of Capacity Building on Emotional Intelligence and Counterproductive Work Behaviors: Evidence from FATA Secretariat, Pakistan - DR. QADAR BAKHSH BALOCH; SHEIKH RAHEEL MANZOOR; FAROOQ HUSSAIN (Journal of Business & Tourism, 2021)
This study aim the capacity building practices intrusion on emotional intelligence and counterproductive work behavior about the staff members of FATA Secretariat, Pakistan. The study incorporated questionnaires as a survey tool for data collection among the individual respondents on cross-sectional basis. Two statistical software’s namely SPSS and Liseral were utilized to analyze the collected data. Reliability and validity of the survey tool was checked through confirmatory factor analysis and found ideal. Structure equation modeling was integrated to tartan 3 devotee variables and was also found good. Result of the study depicts that there exists direct positive path among predictors and response variable. Suggestions and future research indications are also included in the study.